Knowledge, Perspectives and Practice Patterns of Eye Care Providers in Pakistan Regarding Myopia - Muhammad Aamir Shahzad, Hashim Ali Khan, Muhammad Sohail Arshad, Muhammad Sharjeel, Nasir Yasin, Smaha Jahangir, Syed Muhammad Umar Farooq Bukhari, Muhammad Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To survey eye-care professionals in Pakistan, including optometrists, ophthalmologists, and residents from either, on their knowledge, opinions, and clinical practice patterns. We also looked to see if their myopia-related practice habits were in accordance with current standards of care and guidelines. Methods: An online survey was created and shared with eyecare providers from all provinces in Pakistan. The responses were collected over a span of 8 weeks. Results: 173 professionals took part in the survey and 146 were able to complete the survey (based on their response to specific questions). Most common method of refraction was cycloplegic refraction, and most tended to under-correct myopia. Only 1/4th of clinicians were measuring axial length and 21% never performed binocular testing and checked lag of accommodation in myopes. Most common method of myopic fundus examination was dilated fundus biomicroscopy and criteria for peripheral fundus examination was myopia greater than 6 diopters. Almost half have not attended a course/ workshop on myopia (control) in past 6 months and 1/4th tended to rarely read a myopia related journal article. Progression of more than 1 diopter a year was criteria for initiation of control strategies for most clinicians and 0.01% atropine was the preferred initial concentration and almost half of them believed the control strategies to be moderately effective. Conclusion: A substantial proportion of eyecare providers do not appear to be aware of current concepts and do not incorporate recent guidelines into their practices regarding myopia management.